Endemic infectious cutaneous ulcers syndrome in the Oti Region of Ghana: Study of cutaneous leishmaniasis, yaws and Haemophilus ducreyi cutaneous ulcers. - Richard Adjei Akuffo (PLoS ONE, 2023)
Background A recent study detected cutaneous leishmaniasis (CL) in 31.9% of persons with skin ulcers in the Oti Region of Ghana, resulting in a need to investigate other potential causes of the unexplained skin ulcers. Methodology/principal findings A community based cross-sectional study was conducted in the Oti region to investigate skin ulcers of undetermined aetiologies. To confirm a diagnosis of cutaneous leishmaniasis, Buruli ulcer, Haemophilus ducreyi ulcers, or yaws, DNA obtained from each patient skin ulcer sample was systematically subjected to polymerase chain reaction (PCR) for Leishmania spp., Mycobacterium ulcerans, Haemophilus ducreyi, and Treponema pallidum sub species pertenue. A total of 101 skin ulcer samples were obtained from 101 persons. Co-infection of more than one organism was observed in 68.3% of the samples. Forty (39.6%) participants had a positive result for Leishmania spp., 68 (67.3%) for Treponema pallidum sub. Sp. pertenue, and 74 (73.3%) for H. ducreyi. Twenty (19.8%) of the patient ulcers were simultaneously infected with Leishmania spp., Treponema pallidum sub. Sp. pertenue, and H. ducreyi. None of the patients' lesions yielded a positive result for Mycobacterium ulcerans. Conclusions/significance This study detected single and mixed occurrence of the causative organisms of CL, yaws, and H. ducreyi cutaneous ulcers in CL endemic communities of the Oti Region in Ghana. These findings emphasize the importance of integrating multiple skin diseases on a common research platform and calls for the development of a comprehensive guideline for diagnosing and treating tropical ulcers in the study areas.